The onerous consequences of pregnancy and childbirth - Tobiasz, Michał; Turkosz, Agnieszka; Tobiasz, Maciej; Polski, Paweł; Wójcik, Rafał (Journal of Education, Health and Sport, 2019)
Pregnancy is a physiological condition characterized by changes in the functioning of the female body. These changes, referred to as pregnancy adaptation, are necessary both for the development of the foetus and are an expression of the mother’s defense against an invasion of the tissues of the foetus egg, which is harmful to her body. Large adaptive changes in anatomy, physiology and metabolism determine the proper course of pregnancy and childbirth. Unfortunately, there are also negative effects of these changes - weakened tissues, increased intraabdominal pressure, irreversible changes in the whole body. [16] Childbirth (especially vaginal) leads to damage to the fascial-muscular-nerve structures. These structures ensure proper statics and function of the pelvic floor, and their damage may cause functional abnormalities. [8]